Engaging Adolescent and Young Adults in Microbiome Sample Self-Collection: Strategies for Success. Issue 3 (July 2021) - Chen, Chen X.; Carpenter, Janet S.; Murphy, Tabitha; Brooks, Patricia; Fortenberry, J. Dennis
Human microbiome research provides rich opportunities to elucidate factors influencing health, uncover novel biomarkers, and expand disease treatment options. A well-conducted microbiome study depends not only on a rigorous design but also on successfully engaging participants in collecting quality samples. In this paper, we aim to describe (1) strategies our team used to engage adolescents and young adults in vaginal and gut microbiome sample self-collection and (2) their effectiveness. In our prospective, longitudinal, feasibility study of 20 female adolescents and young adults, research participants self-collected vaginal and gut microbiome samples at home. Using a participatory and iterative process, we developed strategies to engage participants in sample self-collection, including (1) providing clear instructions to ensure comprehension and buy-in, (2) providing a user-friendly take-home package, (3) minimizing disgust/embarrassment associated with sample collection, and (4) follow-up communications to facilitate sample collections and return. With these strategies, we achieved 100% participant retention and 100% sample return rates. All samples ( n = 80, 100%) were usable for downstream 16s rRNA gene sequencing and analysis. All participants rated the study procedures as acceptable, and qualitative data showed that strategies were well received by participants. This study suggests that carefully planning and implementing strategies to engage participants in sample self-collection can result in high degrees of participant compliance, sample quality, and participant satisfaction in microbiome research.